EFFECT OF TIME AND SAVE TEMPERATURE TO THE DIFFERENT QUALITY FRESH CEMENT GOAT BEANS - Muhammad Toriqillah (Jurnal Sains Peternakan, 2014)
This study aims to determine the semen quality of fresh Goat Beans on the storage temperature of 5oC to save a different time without the use of diluents. The research was conducted at the Laboratory of the Faculty of Animal Husbandry at the University of Malang Kanjuruhan 6 to February 11, 2012. The method used is the method of experiment by using Completely Randomized Design (CRD) factorial. Research materials used were Beans Goat fresh semen. Based on the results showed that the quality of spermatozoa Goat Beans at 5oC temperature with different long shelf without diluents showed a very noticeable difference (P <0.01). On observations of spermatozoa motility and viability of the Goat Beans 5oC temperature either without using a diluents or diluents showed a very noticeable difference (P <0.01). But the observations did not show any abnormality influence the use of diluents (P> 0.01) and no interaction effect between time savings and the use of diluents to the Goat Beans spermatozoa abnormalities (P> 0.01). Conclusions obtained from the results of this study is that the storage of fresh cement goat beans at a temperature of 50C without the use of a diluents having the best quality that can last up to 42 hours old store.Keywords: time, save temperatur, different quality, fresh cement